Low-Cost Broadband Connections: A Key Factor for SME Virtual Organizations - Odysseas Sakellarides; Vassilis Angelis; George Dounias; Iason Koufodontis (European Regional Science Association (ERSA), 2006)
In an open global market, SMEs are facing new challenges while trying to compete with large worldwide corporations. The forming of innovative alliances, known as virtual organizations (VO), is one of the most interesting proposals to achieve competitiveness and exploit strategic advantages. However, besides the obvious positive potential of innovative actions like VOs, there are several drawbacks, especially when SMEs are involved in such projects. VOs have very high needs for IT and communications; in fact they rely so much on them that the forming of a VO is only possible with the development of an extensive information and communication infrastructure. A lot of innovating management, re-forming and re-structuring is involved in joining several independent companies into a new virtual schema and several cultural, economical and legislative problems must also be overcome. In this paper we focus on the technological needs, and in particular, the need for an organization-wide data sharing and communication network. The high cost involved with the investments necessary in IT and communications technology make the effort harder for SMEs, even if it was to be assumed that they could manage the other important aspects of forming a VO. Along with the cost of computer equipment and specialized software, networking cost has until recently been a particularly prohibiting factor for SMEs even on the most advanced business sectors. A new term, the "virtual organization technology threshold" is introduced, defined as the minimum of IT and communication technologies necessary to form a "true" virtual organization, in its pure and functional form described and widely adopted by the scientific community. The investments needed for IT and communications to form a VO are analyzed and compared to the related investments of conventional SMEs in EU. The evolution in the cost, focused around the networking tools, is then examined to extract useful information about the feasibility of such specialized investments compared to the overall investment and turnovers of typical SMEs. We then argue that a recent development, the price drop and wide spread of broadband connections can act as a "key factor" that could make the difference in lowering the "threshold" and increasing the possibilities for SMEs to compete successfully by utilizing technological advantages and innovations that have until now considered to be more suitable for larger enterprises.
Keywords: 330